2021
DOI: 10.1166/jmihi.2021.3325
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Ultrasound Signs of Scar Pregnancy in Patients with Cesarean Section and Their Clinical Outcomes

Abstract: Caesarean scar pregnancy is the implantation of fertilized eggs in the scar of the previous cesarean section in the lower uterus. It is a serious long-term complication after cesarean section. Ultrasound examination, as the first choice to evaluate cesarean scar pregnancy plays an important role in its diagnosis, treatment and follow-up. This study first tried to propose new ultrasound diagnostic indicators to distinguish cesarean scar pregnancy from non-scar pregnancy of the lower uterine cavity; Logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…By conducting analysis from a theoretical point of view, it is found that factors capable of triggering primary decidual dysgenesis or secondary endometrial damage, such as adenomyosis, uterine malformation, induced abortion, and endometrial infection, may cause placenta accreta. Based on the findings of relevant studies at home and abroad [ 12 – 14 ], it is generally believed that advanced maternal age, cesarean delivery, induced abortion, placenta praevia, and history of uterine surgery are high-risk factors for triggering placenta accreta, of which placenta praevia and cesarean delivery are the most significant, while advanced maternal age and placenta praevia are considered to be two independent risk factors for placenta accreta. Among 108 patients with suspected placenta accreta, 75 with pathologically confirmed placenta accreta were included in the accreta group, and 33 without placenta accreta were included in the non-accreta group; no statistical between-group differences in patients' age, gestational weeks, educational degree, and other general data were observed ( P > 0.05), but the history of cesarean section, history of induced abortion, and the incidence rate of placenta praevia were significantly higher in the accreta group than in the non-accreta group ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…By conducting analysis from a theoretical point of view, it is found that factors capable of triggering primary decidual dysgenesis or secondary endometrial damage, such as adenomyosis, uterine malformation, induced abortion, and endometrial infection, may cause placenta accreta. Based on the findings of relevant studies at home and abroad [ 12 – 14 ], it is generally believed that advanced maternal age, cesarean delivery, induced abortion, placenta praevia, and history of uterine surgery are high-risk factors for triggering placenta accreta, of which placenta praevia and cesarean delivery are the most significant, while advanced maternal age and placenta praevia are considered to be two independent risk factors for placenta accreta. Among 108 patients with suspected placenta accreta, 75 with pathologically confirmed placenta accreta were included in the accreta group, and 33 without placenta accreta were included in the non-accreta group; no statistical between-group differences in patients' age, gestational weeks, educational degree, and other general data were observed ( P > 0.05), but the history of cesarean section, history of induced abortion, and the incidence rate of placenta praevia were significantly higher in the accreta group than in the non-accreta group ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%